Public finance structure and inclusive growth - Cournède, Boris (OECD Economic Policy Papers, 2018)
Tax and spending reforms offer numerous opportunities to promote inclusive growth. There is potential for so-called win-win reforms that simultaneously boost economic output and enhance income equality. Other changes in the structure of public finances will produce benefits only along a single dimension, while some involve trade-offs between average income gains and adverse distributional effects. Empirical analyses of the experience of OECD countries provide evidence about which tax and spending reforms influence prosperity and income distribution -- and by how much